Mechanical model for double side self-propelled rolling machine based on rigid and flexible contact dynamics - Li, Yiming; Liu, Yu; Yue, Xiang; Li, Zhongqiu; Liu, Xingan; Li, Tianlai (International Journal of Agricultural and Biological Engineering, 2022)
The objective of the present research was to establish a mechanical model to study the performance of double side self-propelled rolling machine. There are two key models in the modeling process. The first model is the soft cover dynamics model, which is an important innovation in this study. And the insulation quilt was established based on the Macro-modeling technology. The second model is the double side self-propelled rolling machine virtual prototype model. By specifying multiple contact constraints and loadings between the soft cover dynamics model and the rigid component, the virtual prototype model was built successfully and the double side self-propelled rolling process was completely simulated. Moreover, the interaction mechanisms of the rigid and flexible coupling mechanics were investigated. The virtual rolling processes of different insulation quilt lengths were analyzed under different thickness treatments. The simulated results showed a good agreement with the experiment measurements, which suggested that the established model is an effective approach to evaluate and optimize the rolling machine. The successful establishment of the mechanical model can facilitate the study of the performance of the product and further optimization, and also is of great significance to shorten the development cycle and reduce costs.Keywords: contact dynamics, solar greenhouse, self-propelled rolling machine, mechanical modelDOI: 10.25165/j.ijabe.20221506.6485Citation: Li Y M, Liu Y, Yue X, Li Z Q, Liu X A, Li T L. Mechanical model for double side self-propelled rolling machine based on rigid and flexible contact dynamics. Int J Agric & Biol Eng, 2022; 15(6): 38–43.